Rehat Dulu: Healthy youth mentoring for boarding school girls group at Muhammadiyah 2 senior high school - Priharwanti, Ardiana; Isrofah, Isrofah; Indriyani, Yulis; Budi Prasetyo, Eko (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Adolescence is a colorful and dynamic period, accompanied by a series of emotional upheavals that adorn the journey of a human being about to grow up. Adolescents, the largest age group in the Indonesian population structure, are the focus of attention and a strategic intervention point for human resource development. The most important step that must be taken is to increase attention to adolescent girls, because they face greater risks and are more vulnerable to the social environment. In addition to being the largest group (23% of the total population), adolescents have never received comprehensive and consistent attention. The group of adolescents who are in Islamic boarding schools or pondok environments, also known as boarding schools, are groups that often receive less attention, especially in terms of health. Reproductive health and mental health in adolescent girls are issues in Islamic boarding schools or pondok environments. Reproductive health is a state of perfect physical, cognitive, and social health, not only in the absence of disease or disorders, but also in terms of sexual and reproductive well-being. This includes the right of every individual to have a safe, satisfying, and fulfilling sexual life, as well as the right to have the ability to reproduce and the freedom to decide their own will in terms of reproduction without discrimination, pressure, or coercion. Adolescent reproductive rights are increasingly becoming an important topic to study in the modern era. This community service program aims to provide health education on reproductive health, mental health, and PHBS through "take a break" assistance. The purpose of implementing this program is for groups of students to be independent and effective in improving their health status through increased knowledge and changes in good practices, as a result of the program in the form of improving the quality of services to the community (groups of students) and scientific publications.